Pelatihan Pembuatan Laporan Keuangan menggunakan Microsoft Excel Bagi Mahasiswa yang Berwirausaha - Umar, Ardin; Gafur, Anuwar Kadir Abdul; Hasan, Jamiludin (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The Community Service (PkM) activity with the title "Training on Financial Report Making using Microsoft Excel for Entrepreneurial Students" was carried out by a team of lecturers from the Faculty of the Faculty of Economics, University of Pacific Morotai. The target of this activity is students of the Faculty of Mathematics and Natural Sciences and the Faculty of Economics of the University of Pacific Morotai. The training took place at the Computer Laboratory of the University of the Pacific Morotai Campus with the aim of improving students' ability to manage financial statements using Microsoft Excel effectively and efficiently. The methods used in the training include presentations, demonstrations, and hands-on practice that are intensively guided by the teaching team. The results of this activity showed an increase in participants' ability to prepare financial reports as well as a deeper understanding of the importance of financial management skills in the digital era. This training is expected to have a positive impact on job readiness for entrepreneurial students in the field of finance and information technology.